2017
DOI: 10.1007/s12094-016-1604-z
|View full text |Cite
|
Sign up to set email alerts
|

Activity of weekly paclitaxel−cetuximab chemotherapy in unselected patients with recurrent/metastatic head and neck squamous cell carcinoma: prognostic factors

Abstract: WPC activity was confirmed as a useful therapy on real-life unselected RM-SCCHN patients, with similar benefit to that obtained in the phase II study, and comparable to platinum and cetuximab based treatment, confirming its value in unfit patients. In addition to treatment response, a change in serum magnesium values during treatment was proved as independent PF on OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Common adverse events. PFS of 3.9-7.7 months, and median OS of 7.6-16.8 months(8)(9)(10)(11)(12)(13)(14)(15)(16). The results of our study are consistent with those of previous studies.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Common adverse events. PFS of 3.9-7.7 months, and median OS of 7.6-16.8 months(8)(9)(10)(11)(12)(13)(14)(15)(16). The results of our study are consistent with those of previous studies.…”
supporting
confidence: 92%
“…Recently, the combination of taxanes and Cmab, for example, exchanging 5-FU for taxanes in the Extreme regimen, has drawn attention (7). Cmab and paclitaxel combination therapy (Cmab-PTX), first reported by Hitt et al (8), is one such combination, and some studies have reported that Cmab-PTX has good efficacy for R/MHNSCC patients (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, the prognostic factors associated with Cmab-PTX have been inadequately reported (9,10).…”
mentioning
confidence: 99%
“… 10 Especially, 5-FU was associated with cardiac toxicity and other life-threatening side effects, as well as with high mortality rates. 9 - 11 …”
Section: Introductionmentioning
confidence: 99%
“…A cetuximab-taxane regimen could confer benefit in this patient population. Indeed, the combination of cetuximab plus docetaxel or paclitaxel has been shown to have a manageable safety profile and promising efficacy in various prospective and retrospective studies of patients with either first-line or platinum-refractory R/M SCCHN (Table 4) (2, 5860). Although these studies had small numbers of enrolled patients and were single arm or retrospective, the results suggested that patient selection for cetuximab-plus-taxane combinations in the settings of cisplatin/carboplatin unsuitability or poor PS may result in high ORRs and disease control in certain poor-prognosis populations.…”
Section: Uses Of Cetuximab Plus a Taxanementioning
confidence: 99%